PENGARUH VARIASI KONSENTRASI EKSTRAK SERAI (Andropogon nardus) TERHADAP MORTALITAS HAMA KEONG MAS (Pomaceacaniculata L.) - Putra, Sang; Zein, Suharno (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Snails (Pomaceae canaliculata L) or often referred to as snail mulberry is one type of freshwater snail that comes from the Americas. The spread of snails (Pomaceae canaliculata L.) in Indonesia the spread widening due to breeding very fast. Besides, many snails are farmed in ponds so many move to the rice fields. Potential snails can cause crop damage ranges from 10-40%. The aim of this study was to determine the concentration of extract of lemon grass (Andropogon nardus) most appropriate for mortalty pest snails (Pomacea caniculata L.). This study was conducted in July to September 2014 in Biology Laboratorium State Islamic Institute (IAIN) Raden Intan Lampung. This type of research is experimental. The method used in the study is the method of full randomized design (CRD) with three repetitions each cup contains 12 heads snails. The concentration of treatment were 0% (as a control), 2%, 3%, 4%, 5%. Based on the results of the study showed that:The concentration of the most effective in killing pests snails Pomacea caniculata L is 5%, which is able to kill 100% of pest snails Pomacea caniculata L for 24 hours. Sitronela compounds have the nature of a contact poison that can cause death due to loss of fluid continuously.Kata kunci: Mortalitas, ekstrak, kontak racun.